Transconjunctival Lower Eyelid Blepharoplasty with Volume Augmentation for Correction of the Lower Eyelid and Cheek Junction - Asaria, Jamil (Facial Plastic Surgery, 2023)
Aesthetic surgical management of the inferior periorbital region should include an approach to volume augmentation of the midface and infraorbital hollow, reduction of fat pseudoherniation in the lower eyelids, and treatment of the overlying skin. A combined approach using volume augmentation with fat grafting, a transconjunctival approach to the lower eyelid fat pads, and conservative management of the lower eyelid skin can produce optimal aesthetic results while minimizing complications. Fat harvest from the thigh and abdominal region allows for ample grafting material to the lateral cheek, midface, and orbital rim. The treatment paradigm is to restore volume optimally while minimizing fat resection in the lower eyelids. Volume augmentation is used to restore youthful contours, as well as to counter deflation and laxity in the periorbital and midfacial regions.
Keywords: blepharoplasty; fat grafting; transconjunctival; eyelid surgery